PENDIDIKAN KEWIRAUSAHAAN DENGAN PEMODELAN WIRAUSAHA - Wiedy Murtini (Jurnal Ilmu Pendidikan, 2012)
Abstract: Entrepreneurship Education with Entrepreneurs Modelling. The main objective of the study was to develop a model of the entrepreneurship education programs at the universities. It includes describing; (a) the success stories of entrepreneurs in handling their business who were chosen as the model for the educational program, (b) the entrepreneurship course outline based on the chosen successfull entrepreneurs, and (c) validate the entrepreneurship course design being developed. After doing some try-outs, the course outline and materials were revised. The implementation of the model has shown significant increase in the tendency of the students to develop their entrepreneursip after they take the respective course using the model.